Delimitación Económica en los daños materiales causados a través del Delito de Daño a Bien Ajeno, necesidad de clasificarlo entre delitos y contravenciones. - Torres Peralta, Bryan Fabricio (2024)
The present curricular research work entitled "Economic Delimitation in the material damages caused through the Crime of Damage to Property of Others, the need to classify it between crimes and misdemeanors", was developed because, within our Organic Integral Penal Code, there is no objective delimitation of the economic amount in the offense of damage to property of others. It has been determined that, since there are no clear economic parameters in the law for this type of infractions, it is not possible to classify them as crimes or misdemeanors, and this results in the saturation of crime reports in the Attorney General's Office, making it difficult to achieve effective judicial protection for the victims of this type of infractions, since the property is considered of a small amount. In the case of offenses involving damage to another's property, it is observed that the procedure that governs is the ordinary one, which is subject to be extensive and cumbersome, for the compensation of the damaged property of others of minimum amount, therefore, within the research study, it was also suggested the application of the expedited procedure, which would contribute to achieve efficiency, effectiveness and procedural speed in the administration of justice, always respecting the constitutional principles of legality, proportionality, minimum criminal intervention and fragmentation. For this reason, the aim is to include within article 204 for damage to another's property an economic delimitation, as long as the amount of the damaged property is less than or equal to one basic salary of the worker, in this way the infractions of small amount would be framed as a contravention and could be developed within the expedited procedure, and on the other hand, if the damaged property is greater than the proposed amount, this infraction could be considered as a crime. For the development of this curricular research project, different research parameters were established, such as legal, doctrinal, conceptual. The type of research carried out was mainly bibliographic, and methods such as deductive, inductive, comparative and analytical were also needed. Techniques such as surveys and interviews were also applied, which allowed to obtain criteria from professionals specialized in criminal law, with the purpose of evidencing the problem and therefore provide a solution to incorporate within the infraction of damage to another's property as an objective element an economic delimitation to other people's property of small amount, and to punish them as a contravention through the special expedited procedure.